Research on Postoperative Scar Quality of Sutures and Skin Surface Adhesives - Nao Aburakawa; Yuriko Saito; Ayako Higuchi; Keiichiro Iida; Naoko Wada; Makoto Mikami; Satoshi Urushidate (Journal of Plastic and Reconstructive Surgery, 2025)
Objectives: This study aimed to compare the quality of scarring of DERMABOND PRINEO (Ethicon, Inc., Somerville, NJ, USA)Ⓡ by conducting a half-side test on the same wound to determine its superiority. If the utility of DERMABOND PRINEOⓇ is established, its use can be expanded for more cases and higher quality medical care can be provided. Methods: Patients who underwent two-stage breast reconstruction were included. The first surgery was half closed with DERMABOND PRINEOⓇ and nylon threads, and the time was measured. At the second surgery, all scars were removed, and a histopathological examination was done. Scars were evaluated with the Vancouver Scar Scale (VSS) and visual analogue scale (VAS), and statistical analysis was performed. Results: Time to closure was significantly shorter in the DERMABOND PRINEOⓇ group. Postoperative VSS scores for pliability were significantly lower in the suture group, and the total VSS score was significantly lower in the suture group from 3 to 6 months postoperatively. Patients rated postoperative wound pain, itching, appearance, and satisfaction with the VAS, but no significant differences were observed between the two groups. The scars were compared with hematoxylin-eosin staining and Elastica van Gieson staining. Differences were seen in the increase of elastic fibers in the dermal reticular layer, a characteristic difference between the two groups. Conclusions: The use of DERMABOND PRINEOⓇ leads to a reduction in operative time and impacts the maturity of the scar. It is expected that the indications for DERMABOND PRINEOⓇ can be further expanded in the future.